SISTEM PERADILAN DI INDONESIA BERDASARKAN UUD NEGARA REPUBLIK INDONESIA TAHUN 1945 - Subihat, Ihat (Yustitia, 2019)
A country’s judicial system cannot be separated from the legal system in force in the country. In other words, a country’s justice system is a sub-system of the country’s justice system. Because the legal system that applies in Indonesia is a legal system based on the Pancasila and the 1945 constitution of the Republic of Indonesia, the judicial system in Indonesia must also be based on Pancasila values and articles in the 1945 Constitution of the Republic of Indonesia. This study was conducted by using normative juridical method by reviewing various legal materials; primary, secondary and tertiary legal materials. While the data collection method was carried out through library studies. The analysis technique used descriptive method with prescriptive approach. The result of this study showed that the four judicial environments are under the Indonesia Supreme Court; general justice, religious justice, military justice and state administrative courts, as sub-judicial systems in Indonesia, each of which has an institutional, authority and legal structure separate events that differ from one another according to the specificity and absolute competence of each that cannot be mixed up. In contrast to other judicial environments which have adjusted to the changes in the new judicial power law, the institutional structure and authority of the courts within the military court which is part of the judicial system under the Supreme court of the Republic of Indonesia is still regulated in Law Number 31 of 1997 concerning Military justice and not yet adjusted to Lay Number 14 of 2004 concerning Judicial Power, because the Amendment Draft to the Law on Military Justice which had been discussed since 2005 has not yet been agreed upon by the DPR and the Government. Even when the Lay on Military Justice cannot be adjusted to Law Number 4 of 2004, on October 29, 2009 Law Number 4 of 2004 was revoked and then replaced with Law Number 48 of 2009 concerning the latest Judicial Power.